Anticipation of COVID-19 Vaccines Reduces Social Distancing - Ola Andersson; Pol Campos-Mercade; Armando N. Meier; Erik Wengström (Lund University, School of Economics and Management, Department of Economics, 2020)
We show that the anticipation of COVID-19 vaccines reduces voluntary social distancing. In a large-scale preregistered survey experiment with a representative sample, we study whether providing information about the safety, effectiveness, and availability of COVID-19 vaccines affects compliance with public health guidelines. We find that vaccine information reduces peoples' voluntary social distancing, adherence to hygiene guidelines, and their willingness to stay at home. Vaccine information induces people to believe in a swifter return to normal life and puts their vigilance at ease. The results indicate an important behavioral drawback of the successful vaccine development: An increased focus on vaccines can lead to bad health behaviors and accelerate the spread of the virus. The results imply that, as vaccinations start and the end of the pandemic feels closer, existing policies aimed at increasing social distancing will be less effective and stricter policies might be required.
Keywords: D83; D91; I12; I18; 330; Economic epidemiology; social distancing; vaccination; information